Fracture Mechanics and Fatigue Damage of Materials and Structures - Lesiuk, Grzegorz; Rozumek, Dariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
One of the most important aspects of the engineering assessment of the technical condition of structures and materials is the ability to assess the fatigue behavior of materials and structures. In addition, another important topic is the design of materials or structures that can resist fatigue and fracture. Modern science provides us with an increasing number of new materials, from superalloys of metals manufactured conventionally as well as via additive manufacturing to functionally advanced composites. Against this background, fundamental knowledge of the fatigue behavior and fracture mechanics of different material groups provides a convenient platform for communication between different interested groups and fields: from material science, numerical engineering and mathematical modeling to hybrid methods for fatigue life prediction. This Special Issue facilitates such an exchange of ideas on recent developments in the field of fatigue and fracture and is especially focused on fatigue crack growth analysis, the description of fatigue damage in metals and composites, probabilistic approaches and fracture mechanics analysis, as well as fatigue failure analysis and lifetime prediction.